The European Union's Trade Relations with Australia - Ludmila Borta (CES Working Papers, 2013)
The European Union is a major player in the world economy and also the largest trading player on the global scene, accounting for about 20% of world imports and exports. The elimination of trade barriers within the EU confirmed its commitment to global trade liberalisation as it is an important part of multilateral trade negotiations. Apart from WTO trade agreements, the European Union concluded a number of bilateral trade agreements with certain countries and regions in the world. The aim of this paper is to present the EU-Australia trade relationship, Australia being an important trading partner of the EU. The trade flows between them includes both agricultural and non-agricultural products. The database that has been used is represented by the information published by the European Commission and the Australian Government. In conclusion, we found that both EU imports from Australia and EU exports to Australia are dominated by non-agricultural products.
Keywords: F1; O24; Y10; 330; trade relations; EU's imports; EU's exports; Australia; trade partnership Romania